2018
DOI: 10.1111/epi.14600
|View full text |Cite
|
Sign up to set email alerts
|

Defining the electroclinical phenotype and outcome of PCDH19‐related epilepsy: A multicenter study

Abstract: Summary Objective PCDH19‐related epilepsy is an epileptic syndrome with infantile onset, characterized by clustered and fever‐induced seizures, often associated with intellectual disability (ID) and autistic features. The aim of this study was to analyze a large cohort of patients with PCDH19‐related epilepsy and better define the epileptic phenotype, genotype‐phenotype correlations, and related outcome‐predicting factors. Methods We retrospectively collected genetic, clinical, and electroencephalogram (EEG) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 32 publications
1
55
3
3
Order By: Relevance
“…We also showed that individuals with seizure onset before 12 months of age had more severe ID than those with seizure onset after 12 months 9 . A recent retrospective study validated this finding and also showed an association between earlier seizure onset and the presence of ASD 4 . Reviewed studies were typically based on small samples, lacked systematized approaches, and focused on only one clinical outcome.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…We also showed that individuals with seizure onset before 12 months of age had more severe ID than those with seizure onset after 12 months 9 . A recent retrospective study validated this finding and also showed an association between earlier seizure onset and the presence of ASD 4 . Reviewed studies were typically based on small samples, lacked systematized approaches, and focused on only one clinical outcome.…”
Section: Introductionsupporting
confidence: 58%
“…The hallmark of GCE is clusters of focal seizures, often coinciding with fever 1 . While the seizure semiology associated with GCE has been characterized [1][2][3][4] , the neuropsychiatric profile has not been well established.…”
Section: Introductionmentioning
confidence: 99%
“…Further, PCDH19-positive mutations, also known as epilepsy with mental retardation in females, are invariably linked to a high sensitivity to fever. 16,17…”
Section: Risk Factors To Develop Complex Febrile Seizuresmentioning
confidence: 99%
“…The seizure frequency decreases after the age of 2 and 10 years. 29 Some patients become seizure free at the age of 12 years. This finding is independent of age at seizure onset.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…This finding is independent of age at seizure onset. 29,30 Clinically, the seizures may start with a myoclonic jerk followed by a period of reactivity with a fearful look or startled jerks, followed by mild tonic, asymmetric tremulous-ness movements, and mild clonic activity. This semiological sequence is usually seen associated with PCDH19-related epilepsy.…”
Section: Clinical Featuresmentioning
confidence: 99%